Effect of isoflavones on atherosclerosis in peritoneal dialysis patients - Sahpaz, Fatih; Dogukan, Ayhan; Dagli, Mustafa Necati (Cukurova Univ, Fac Medicine, 2016)
Purpose: Cardiovascular disease is an important cause of morbidity and mortality in patients with renal failure. Patients with chronic renal failure are significantly susceptible to atherosclerosis. Our aim is to investigate the effect of isoflavone upon atherosclerosis and inflammation in continuos ambulatory peritoneal dialysis patients. Material and Methods: Fifty eight patients undergoing peritoneal dialysis were enrolled in the study. The Patients have been separated into two groups. The first group with a plasebo, the second group with 40 mg soy isoflavones (Isoflavin(R), Mikro-Gen) 2 times per day was given to patients during 12 weeks. Two of them because of gastrointestinal side effects leaved the study and the study was completed with 56 patients. Before and after the treatment of isoflavone total cholesterol, triglyceride, LDL cholesterol, HDL cholesterol, hs-CRP, homocysteine, intima-media thickness, arterial stiffness values were measured and statistical analyses was made. Results: The levels of intima-media thickness, arterial stiffness and one of the inflammation marker hs-CRP was statistically lower after the treatment with isoflavones than the beginning of treatment. Conclusion: Finally; it can be supplied useful effects on inflammatory and atherosclerotic process by using of isoflavones which has antilipogenic, antihypertensive and improving vascular health properties in end stage renal disease.
Keywords: Inflammation; peritoneal dialysis; isoflavone; intima-media thickness